2008
DOI: 10.1182/blood-2008-02-138941
|View full text |Cite
|
Sign up to set email alerts
|

A phosphatidylserine binding site in factor Va C1 domain regulates both assembly and activity of the prothrombinase complex

Abstract: Tightly associated factor V(a) (FVa) and factor X(a) (FXa) serve as the essential prothrombin-activating complex that assembles on phosphatidylserine (PS)-containing platelet membranes during blood coagulation. We have previously shown that (1) a soluble form of PS (C6PS) triggers assembly of a fully active FVa-FXa complex in solution and (2) that 2 molecules of C6PS bind to FVa light chain with one occupying a site in the C2 domain. We expressed human factor V(a) (rFVa) with mutations in either the C1 domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 51 publications
5
51
1
Order By: Relevance
“…3A, inset; K d ϭ ϳ3 Ϯ 0.5 nM) compared with the synthetic lipids used in this study. This is consistent with the observation that factor Va binding free energy derives principally from insertion of Trp residues into the membrane (27), an event that should be promoted by the reduced interfacial packing associated with highly unsaturated lipids. Adding 1% PS to 30% DOPE membranes had little effect on factor Va binding, although increasing PS content to 5-10% did improve binding somewhat but not beyond what was observed in the absence of DOPE (Table 2).…”
Section: Membranesupporting
confidence: 76%
See 2 more Smart Citations
“…3A, inset; K d ϭ ϳ3 Ϯ 0.5 nM) compared with the synthetic lipids used in this study. This is consistent with the observation that factor Va binding free energy derives principally from insertion of Trp residues into the membrane (27), an event that should be promoted by the reduced interfacial packing associated with highly unsaturated lipids. Adding 1% PS to 30% DOPE membranes had little effect on factor Va binding, although increasing PS content to 5-10% did improve binding somewhat but not beyond what was observed in the absence of DOPE (Table 2).…”
Section: Membranesupporting
confidence: 76%
“…More extensive experiments are needed to prove this hypothesis. We expect that this is not the case for factor Va 2 , because only the site in the C1 domain regulates the interaction between factors Xa and Va (27). We 2 Binding of soluble phospholipids to 0.1 M rHFVa or 0.1 M human factor Xa was monitored using intrinsic fluorescence intensity in 20 mM Tris, 150 mM NaCl, and 5 mM CaCl 2 , pH 7.5, as a function of C6PS, C6PE, C6PC, or C6(D)PS and the concentration at 23°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that lactadherin, which binds PS with a high affinity and shares homology to the PS-binding domains of FV (30), completely failed to prevent FV uptake (Fig. 1C).…”
Section: Discussionmentioning
confidence: 90%
“…The reported ability of Gal8 to induce PS exposure on the surface of cells (35,36) and the known affinity of FV for PS (30) raised the possibility that the uptake mechanism may be dictated by PS exposure. However, we found that lactadherin, which binds PS with a high affinity and shares homology to the PS-binding domains of FV (30), completely failed to prevent FV uptake (Fig.…”
Section: Discussionmentioning
confidence: 99%